Parent-infant interactions in families with women diagnosed with postnatal depression: a longitudinal study on the effects of a psychodynamic treatment - Tambelli, Renata; Cerniglia, Luca; Cimino, Silvia; Ballarotto, Giulia (Frontiers in Psychology, 2015)
Background: Several studies have shown a connection between mothers with post-natal depression (PND) and emotional-behavioral problems in their children. Mothers' psychopathology may impair interactional patterns with children and these outcomes can be influenced by father's psychopathological symptoms. The primary aim of the study was to assess over time parent-infant interaction in families where mothers have experienced postnatal depression and have received psychological treatment during the child's first year of life considering the severity of parents' psychopathological symptoms and children's temperament. Methods: Three groups of families were involved: families with mothers with PND wherein both parents followed a psychological treatment (TxMF); families with mothers affected by PND wherein only the mother followed the treatment (TxM) and control families wherein the mothers did not have a psychopathological diagnosis and did not receive any treatment (Con). The families were assessed at two time points through Symptom Check-List-90-Revised (SCL-90-R), Questionari Italiani Temperamento (QUIT) and the video-recorded procedure observing mealtime Scala di Valutazione Interazioni Alimentari (SVIA). Results: Parents in the TxMF group had significantly lower SVIA scores (i.e . less maladaptive) at T2. TxMF group scored lower at T2 at SCL-90-R, whereas TxM showed no significant differences between T1 and T2. Involvement of fathers in the treatment was important to improve the psychopathological symptoms of both parents and the quality of interactions with their children.